Differential regulation of sphingolipid metabolism in plasma, hippocampus, and cerebral cortex of mice administered sphingolipid modulating agents. Issue 3 (28th February 2017) - Giles, Corey; Takechi, Ryusuke; Mellett, Natalie A.; Meikle, Peter J.; Dhaliwal, Satvinder; Mamo, John C.
Abstract: Accumulation of ceramide is implicated in mediating the cellular responses to stress and aberrant sphingolipid metabolism is frequently associated with metabolic and neurodegenerative diseases. It is often assumed that (i) peripheral disturbances in sphingolipid concentrations are reflective of processes occurring in the brain, or (ii) circulating sphingolipids directly influence cerebral sphingolipid abundance. In order to address these assumptions, this study explores, in a physiological system, the metabolic pathways regulating sphingolipid metabolism in the brain and plasma of mice. Male C57Bl/6 were maintained on a low fat (control diet) or saturated fat enriched (SFA) diet with, or without the provision of sphingolipid modulating agents. Following 6 months of feeding, the abundance of seven sphingolipid classes was assessed by LC‐ESI‐MS/MS in the hippocampus (HPF), cerebral cortex (CTX), and plasma. Long‐term consumption of the SFA diet increased ceramide and dihydroceramide in the plasma. Inhibiting de novo synthesis ameliorated this effect, while inhibition of acidic sphingomyelinase, or the sphingosine‐1‐phosphate receptor agonist did not. SFA feeding did not influence sphingolipid levels in either the HPF or CTX. De novo synthesis inhibition reduced ceramide in the CTX, while treatment with a sphingosine‐1‐phosphate receptor agonist reduced ceramides in the HPF. Analysis of the individual ceramide species revealed the effects were chain‐length dependent. Both positive and negative correlations were observed between plasma and HPF/CTX ceramide species. The findings in this study show that HPF and CTX sphingolipid concentration are influenced by distinct pathways, independent of peripheral sphingolipid concentration. Abstract : Substantiative evidence suggests sphingolipid metabolism is perturbed early in the development of neurodegenerative disorders. Peripheral sphingolipids are attractive biomarkers for predicting disease risk, however, it is not known how these relate to cerebral sphingolipid homeostasis. Using a suite of sphingolipid modulating agents, we describe the major pathways regulating sphingolipid metabolism in plasma, hippocampus, and cerebral cortex of mice.